Accounting, Audit, and Business Analysis Methodical Tools to Implement the Needs of Financial Information Users - Inna Raikovska; Oleksandr Kostenko; Vadim Ugnivenko (Облік і фінанси)
To make informed decisions, users of financial information need to achieve a certain level of trust in its indicators. The main means of ensuring such trust is verifying information through accounting, audit, and business analysis procedures. The article aims to analyze a system of methods that will increase financial data's accuracy, objectivity, reliability and transparency, which is the basis for making management decisions. Awareness of economic changes has become the basis for recognizing financial information as a constantly changing object. In the context of growing requirements for its reliability and sufficiency for making management decisions in conditions of uncertainty, financial information formed in the accounting system becomes an important object of audit and business analysis. The article identifies the main types of financial information studied in its users' interests, such as historical, forecast and hypothetical financial information. In addition, the work presents the substantive characteristics of financial information for making effective management decisions on economic activities. The results of the study indicate that effective management decisions of users of financial information are possible due to proper assessment of the procedures for creating appropriate media by responsible persons according to criteria related to compliance with the requirements for systematization of objects characterized by financial information, as well as compliance with the procedures for timeliness and completeness of providing access to it. The information needs of users of financial information are formed and simultaneously affect the type of consumer behaviour (random, basic, target, evaluative, functional), the timely identification and consideration of which are essential when planning and conducting an audit of financial information.